INVESTIGATION OF SORPTION PROPERTIES OF NEW POLYMER SORBENTS BASED ON N-SUBSTITUTED MALEIMIDES - Batueva, T.D.; Gorbunova, M.N.; Scherban, M.G. (Perm Federal Research Centre Journal, 2014)
Sorption properties of copolymers based on substituted maleimides have been investigated. A possibility to extract rhenium (VII) ions from aqueous solutions by means of copolymers under investigation has been revealed. In combined presence of Re (VII) and Mo (VI) ions in acidic and alkaline mediums as solutions, rhenium can be separated from molybdenum by ionites under investigation.